FISCAL POSITION OF THE UNION BUDGET IN INDIA DURING COVID-19 - Mudasir Ahmad Ganai (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
The present study analyzes the fiscal position as an instrument to measure the amount of government borrowing to require the financial position and their budget shortfall. This study traces the major current changes in the Indian fiscal system during the period 2019-22, though the union's Government adopt the fiscal rule to reduce the financial crisis during the epidemic period of Covid-19. However, the current study also traces the percentage of GDP decrease because of the problem of lockdown during Covid-19 and also studies the budget position in India. The paper concludes with a discussion on the composition of union government receipts and expenditure position in the current scenario and indicated the situation of fiscal and revenue deficit of the government budget. Finally argue that subsidy rationalization is the way forward to fund the much-needed health expenditures and transfers while maintaining fiscal discipline.